2015
DOI: 10.3390/educsci5020104
|View full text |Cite
|
Sign up to set email alerts
|

A Blended Learning Approach to Teaching Project Management: A Model for Active Participation and Involvement: Insights from Norway

Abstract: Abstract:The paper demonstrates and evaluates the effectiveness of a blended learning approach to create a meaningful learning environment. We use the term blended learning approach in this paper to refer to the use of multiple or hybrid instructional methods that emphasize the role of learners as contributors to the learning process rather than recipients of learning. Contribution to learning is attained by using in class gaming as pathways that ensure active involvement of learners. Using a blended learning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 56 publications
2
42
0
6
Order By: Relevance
“…allows students to obtain immediate formative feedback on their learning without posing any risk of embarrassment (Hussein 2015). This has been evident in our student feedback with comments such as: Previous research has indicated that Kahoot scores highly on student satisfaction and enjoyment of their classes (Hussein 2015). In a large module consisting of just under 300 students, we found through their module evaluations that a favourite aspect of the module was the interactive quizzes.…”
Section: In-class Technologiesmentioning
confidence: 59%
“…allows students to obtain immediate formative feedback on their learning without posing any risk of embarrassment (Hussein 2015). This has been evident in our student feedback with comments such as: Previous research has indicated that Kahoot scores highly on student satisfaction and enjoyment of their classes (Hussein 2015). In a large module consisting of just under 300 students, we found through their module evaluations that a favourite aspect of the module was the interactive quizzes.…”
Section: In-class Technologiesmentioning
confidence: 59%
“…The researcher found these two claims to be true based on his observation of the participants' behaviour throughout the process in which they were observed to be very engaged and motivated. This experience also proved Hussein's (2015) statements on gamification domains that there is a high chance that this achievement is also driven from the…”
Section: Findings and Discussionmentioning
confidence: 54%
“…This element of unconscious learning would be very fitting with this study especially in applying the irregular verbs learning which is said to be prompted even before than the regular verbs. Hussein (2015) highlights four key domains on how gamification benefitted the learners. Among the two domains involved learners especially the young ones see this approach rather more entertaining and fun hence lowering their affective filter and keep the engagement level at bay.…”
Section: Literature Reviewmentioning
confidence: 99%
“…(3) Motivates students to learn given by Warnich and Gordon (2015). (4) Quick assessment of students in short time (Hussein (2015). (5) Increase teacher/students communication given by Stone (2014).…”
Section: Rq4: What Benefits and Challenges Are Perceived By The Teachmentioning
confidence: 99%